Organizing and Sustaining Inclusive Learning Environment: International Practices - Sydoriv, Sergiy (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Teacher training in different countries has its peculiarities. Principles of inclusive education are universal, yet existing societal beliefs and values, policy and hidden curriculum in schools and preschool, parental support and advocacy demand taking them into account. In orderto adhere to the principles and ideas of inclusive education teachers should be able to organize and sustain inclusive learning environment in their classrooms and outside. It is researched that many countries have long history of including students with special educational needs and disabilities and their experience may be viable for teachers’ trainers, administrators and educators in those countries who has just started inclusion on a national level. Sharing the best practices and strategies and adapting them to the local peculiarities is the key to successful inclusion students with disabilities. The article gives various examples of how scholars define inclusive learning environment, what its characteristics and components are. International legislation, which proclaims the right of a person to education and regulates inclusion is the model for national laws as well it is developed and influenced by them. The study identifies legislative models for implementing Article 24 of the CRPD consistent with its principles and obligations and suggests the priorities to be incorporated into domestic legislations. It is highlighted that every country has stories of success, best practices, which may prove highly effective, applied to educational systems of other countries. Therefore, as proved it is important to exchange these practices, conduct research and gather evidence to create effective inclusive learning environment and train pre-service and in-service teachers to organize and sustain it.